(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article deals with the philosophical works of oral ecological values; the great mind conconant with ecological imperatives of our time, the distribution of theirfuture generations and the formation of ecological culture.